Postnatal Human Genetic Enhancement – A Consideration of Children’s Right to Be Genetically Enhanced - Tamir, Sivan (Frontiers in Sociology, 2016)
This paper considers children’s rights with respect to genetic enhancement (GE). It is focused on the futuristic prospect of postnatal GE, namely, genetic modifications in vivo, of actual existing individuals. More specifically, the paper examines whether, in a future reality where pre- and postnatal human GE is safely and prevalently practiced, a child would have a right to be genetically enhanced by her parents or guardians, as well as the right not to be genetically enhanced. It is in fact the postnatal phase, inhabited by persons of indisputable moral status, subject of rights against others, which makes the child’s putative right (not) to be genetically enhanced a relevant and legitimate subject of exploration. Since postnatal GE is a futuristic technology, an appropriate, concrete, rights-discourse has not yet been developed. In this paper I therefore, attempt to initiate such discourse, by identifying, through legal analysis, potential sources for the child's right to be genetically enhanced, and theorize theorizing about its nature (derivative, or a newly created independent right; positive or negative right). I begin by considering several (mostly) contemporary candidate core rights, from which the child’s right (not) to be genetically enhanced could potentially derive, ; next, I consider the child’s right not to be genetically enhanced, through ethical analysis; finally, I and then look into the merits of creating such a novel right of the child. I conclude, that the direct translation of the child's interests in being genetically enhanced, into any kind of recognised positive or negative right – whether derivative or a newly emerging independent right – is unlikely. As per the putative child's right not to be genetically enhanced postnatally, I determine that such a right could be recognized as a relative right, balanced against parental autonomy in rearing and shaping one's child.